2020
DOI: 10.36765/jartika.v3i1.25
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Bahan Ajar Matematika Berbentuk Komik untuk Meningkatkan Kemampuan Matematis Siswa Kelas VII SMP

Abstract: Abstrak: Penelitian ini bertujuan mengembangkan bahan ajar matematika berbentuk komik untuk siswa kelas VII SMP. Penggunaan Bahan Ajar dalam proses pembelajaran merupakan salah satu cara untuk membantu siswa dalam memahami materi pembelajaran. Bahan ajar yang diberikan kepada siswa harus memenuhi kriteria valid, praktis, dan efektif.Penelitian ini menggunakan metode penelitian Research and Development R and D) dengan menggunakan model pengembangan Plomp yang terdiri atas fase investigasi awal, fase pengembanga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
1
3
0
1
Order By: Relevance
“…In line with research conducted by Fikriani and Nurva (2020), entitled " Creation of Comic-Shape Teaching Resources for Mathematics to Improve Mathematical Ability of Grade VII Junior High School Students", found that the comics were very valid with a percentage of 90%, very practical with a percentage of 83.5%, and effective for improving students' mathematical abilities with a percentage of 73% [13] . The facts above show that the comics developed help students in learning math, provide motivation and help them learn math.…”
Section: Discussionsupporting
confidence: 76%
“…In line with research conducted by Fikriani and Nurva (2020), entitled " Creation of Comic-Shape Teaching Resources for Mathematics to Improve Mathematical Ability of Grade VII Junior High School Students", found that the comics were very valid with a percentage of 90%, very practical with a percentage of 83.5%, and effective for improving students' mathematical abilities with a percentage of 73% [13] . The facts above show that the comics developed help students in learning math, provide motivation and help them learn math.…”
Section: Discussionsupporting
confidence: 76%
“…Analisis yang dilakukan oleh (Anwar, 2018) untuk meningkatkan proses dan output hasil pembelajaran maka kemampuan untuk mendesain dalam mengembangkan media adalah sebuah keniscayaan. Diuraikan dalam penelitian (Fikriani & Swetherly Nurva, 2020) bahwa dalam pembuatan komik membutuhkan penyesuaian minat dan baca siswa sehingga dapat memotivasi dalam proses pembelajaran. Komik merupakan pilihan yang menarik untuk menjadi media pembelajaran yang melibatkan emosional dalam membacanya.…”
Section: Hasil Dan Pembahasanunclassified
“…According to Gunadi & Aisah (2019), comics can also be used as a learning medium that can train students' mathematical literacy skills to become more developed. Comics are defined as a medium that presents simple stories that are easy to understand, the contents of which are accompanied by cute pictures so that they are liked by many people (Fikriani & Swetherly Nurva, 2020). Comics are used as learning media, and they can motivate students to understand material that is considered difficult to understand quickly and can lengthen students' memory so that they can support students' success in learning mathematics (Mujawal et al, 2018) Based on research by Putra & Milenia (2021), learning media in the form of mathematics comics improves students' problem-solving ability.…”
Section: Introductionmentioning
confidence: 99%